THE IMPLEMENTATION OF LEARNING TASKS IN THE WHEN ENGLISH RINGS A BELL TEXTBOOK FOR THE SEVENTH GRADE STUDENTS OF MTS NEGERI WONOSARI - Riyadi, Agus; Sugirin, Sugirin (Diksi, 2018)
Abstract            (Title: The Implementation of Learning Tasks  in The When English Rings a Bell Textbook  for The Seventh Grade Students of MTs Negeri Wonosari). This research aims to describe the implementation of learning tasks in the When English Rings a Bell textbook. This research was a descriptive qualitative research employing a descriptive and qualitative method of analysis. The subjects were an English teacher and 55 students of VII A and VII F of MTs. Negeri Wonosari in the academic year of 2014/2015. The objects of the research were the learning tasks in the When English Rings a Bell textbook (Chapters VIII and IX). The data were collected through observations, questionnaire, interviews, and document analysis. The data were analyzed using descriptive analysis technique applying the Miles and Huberman Model. The results of the research show that the goal of tasks in Chapters VIII and IX is that the students can develop their vocabulary mastery, and make a simple description of people, animals, and things around them. The materials presented were appropriate since the materials were interesting and close to the real world. The activities applied by the teacher were communication strategies, dialogues and role plays, discussions and decisions making, questions and answers, and exercises. The students participated actively in doing the tasks. The teacher performed his roles as a facilitator, manager, controller, organizer, assessor, prompter, participant, resource, tutor, and observer well. The settings were desks line in rows, horseshoe shape, parallel chair setting, and group to group setting. Keywords: implementation, learning tasks, facilitator, manager, controller.